Evaluation of salivary tumour necrosis factor-alpha in patients with recurrent aphthous stomatitis - Shruthi Hegde; Vidya Ajila; Subhas Babu; Suchetha Kumari; Harshini Ullal; Ananya Madiyal (Istanbul University, 2018)
Purpose Present study was undertaken to evaluate and compare the salivary levels of tumour necrosis factor alpha (TNF-α) in subjects with RAS, traumatic ulcers (TUs) in the oral mucosa and in healthy controls. Materials and Methods Present study involved 90 participants of which 30 subjects were diagnosed with RAS, 30 subjects with TUs and 30 healthy controls grouped as group 1, group 2 and group 3 respectively. Unstimulated saliva was collected from the subjects through 'Spit Technique' and the estimation of TNF-α was done by enzyme linked immunosorbent assay. The data collected was statistically analysed. Results Salivary level of TNF-α was significantly higher in RAS patients than in patients with TUs and healthy controls. Difference between the Salivary TNF-α level in our study groups were statistically significant (p<0.001). Conclusion Present study suggests that saliva is a convenient and ideal medium for the detection of TNF-α. Statistically significant difference in the level of salivary TNF-α between the RAS and TUs subjects as well as controls suggests the significant contribution of TNF-α in pathogenesis of RAS.